2000
DOI: 10.1097/00005344-200004000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-Induced Action Potential Shortening is Blunted by d-Sotalol in a Pig Model of Reversible Myocardial Ischemia

Abstract: The purpose of this study was to investigate, in an anesthetized pig model of low-flow myocardial ischemia, the electrophysiologic effects of the class III drug d-sotalol during myocardial ischemia. Serial monophasic action potential (MAPD90) recordings and refractory period determinations from the anterior and posterior left ventricular wall were taken in 25 pigs during baseline, after low-flow posterior wall ischemia, after d-sotalol infusion under nonischemic conditions, and after repeated posterior wall is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Shortening of MAP duration is the expected response to ischaemia, due primarily to opening of K ATP channels [1]. The magnitude of observed changes was similar to those demonstrated by other investigators in dogs and pigs [4,34].…”
Section: Resultssupporting
confidence: 86%
“…Shortening of MAP duration is the expected response to ischaemia, due primarily to opening of K ATP channels [1]. The magnitude of observed changes was similar to those demonstrated by other investigators in dogs and pigs [4,34].…”
Section: Resultssupporting
confidence: 86%
“…Studies in cats and canine models of ischemia revealed that sympathetic stimulation creates both the electrophysiological substrate and the trigger for VT/VF by reducing action potential duration, increasing dispersion of repolarization, and causing early after depolarizations (EADs) and delayed after depolarizations (DADs), Table . Action potential shortening and increased dispersion of repolarization (as also evidenced by increased T‐peak to T‐end interval) have been demonstrated in chronic porcine infarct models, in response to sympathetic nerve stimulation …”
Section: Pathophysiology Of Ventricular Arrhythmias In Heart Diseasementioning
confidence: 99%
“…[36][37][38] Action potential shortening and increased dispersion of repolarization (as also evidenced by increased T-peak to T-end interval) have been demonstrated in chronic porcine infarct models, in response to sympathetic nerve stimulation. 39,40 Inflammation and ischemia also injure axons of the autonomic nerves, resulting in denervation. Studies in canine models of MI and humans undergoing catheter ablation for recurrent VA demonstrate that denervation is observed within the infarcted myocardium as well as nearby viable myocardium.…”
Section: Va In the Setting Of Myocardial Infarctionmentioning
confidence: 99%